Ecology of Ephemeroptera, Plecoptera and Trichoptera (Insecta) in Rivers of the Gunung Jerai Forest Reserve: Diversity and Distribution of Functional Feeding Groups - Hamid, Suhaila Ab (Penerbit Universiti Sains Malaysia, 2014)
A field study was performed to describe the functional feeding groups (FFGs) of Ephemeroptera, Plecoptera and Trichoptera (EPT) in the Tupah, Batu Hampar and Teroi Rivers in the Gunung Jerai Forest Reserve (GJFR), Kedah, Malaysia. Twenty-nine genera belonging to 19 families were identified. The EPTs were classified into five FFGs: collector-gatherers (CG), collector-filterers (CF), shredders (SH), scrapers (SC) and predators (P). In this study, CG and CF were the dominant groups inhabiting all three rivers. Ephemeroptera dominated these rivers due to their high abundance, and they were also the CG (90.6%). SC were the lowest in abundance among all groups. Based on the FFGs, the Teroi River was suitable for CG, whereas the Tupah and Batu Hampar Rivers were suitable for CG and CF. The distribution of FFGs differed among the rivers (CG, χ(2) = 23.6, p = 0.00; SH, χ(2) = 10.02, p = 0.007; P, χ(2) = 25.54, p = 0.00; CF, χ(2) = 21.95, p = 0.00; SC, χ(2) = 9.31, p = 0.01). These findings indicated that the FFGs found in rivers of the GJFR represent high river quality.